2021
DOI: 10.1093/mnras/stab780
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, scaling relations and physical conditions of ionized gas outflows in MaNGA

Abstract: In this work, we investigate the strength and impact of ionised gas outflows within z ∼ 0.04 MaNGA galaxies. We find evidence for outflows in 322 galaxies ($12{{\ \rm per\ cent}}$ of the analysed line-emitting sample), 185 of which show evidence for AGN activity. Most outflows are centrally concentrated with a spatial extent that scales sublinearly with Re. The incidence of outflows is enhanced at higher masses, central surface densities and deeper gravitational potentials, as well as at higher SFR and AGN lum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 110 publications
4
44
0
Order By: Relevance
“…However, this drop is not uniform as the velocity and flux distributions both show clumpy profiles within the outflowing medium. We note that the outflow across the FoV might not be entirely due to the AGN, as the asymmetry in the [O ] line profile could result from residual turbulence from star formation or supernovae driven winds (e.g., Davies et al 2019;Avery et al 2021;Herrera-Camus et al 2021). The electron density map also shows a non-uniform distribution, similar to the ones observed previously in the literature with lower spatial resolution data (e.g., Kakkad et al 2018).…”
Section: Resolved Mass Outflow Rate Mapssupporting
confidence: 81%
“…However, this drop is not uniform as the velocity and flux distributions both show clumpy profiles within the outflowing medium. We note that the outflow across the FoV might not be entirely due to the AGN, as the asymmetry in the [O ] line profile could result from residual turbulence from star formation or supernovae driven winds (e.g., Davies et al 2019;Avery et al 2021;Herrera-Camus et al 2021). The electron density map also shows a non-uniform distribution, similar to the ones observed previously in the literature with lower spatial resolution data (e.g., Kakkad et al 2018).…”
Section: Resolved Mass Outflow Rate Mapssupporting
confidence: 81%
“…For most of the lines, but particularly H𝛼 and OIIId, there is a large component on the blue side. The strength of this asymmetry is highly unusual, though some asymmetry has been observed in dwarf galaxies with gas outflows or inflows in MaNGA (Wylezalek et al 2020;Avery et al 2021), as well as in some extremely metal-poor dwarf galaxies (EMPGs) in the EMPRESS sample (Kojima et al 2019). This initially suggests that our source is a dwarf galaxy with a gaseous outflow; we investigate this possibility by looking at the components of the flux fit.…”
Section: Spectroscopic Analysis Of Sourcementioning
confidence: 89%
“…Gas outflows powered by AGN may inflate gas velocity dispersions, explaining the correlation between Δ𝜎 and 𝐶 AGN . Avery et al (2021), however, reported that the mass outflow rates depend on the luminosity of AGN and SFR, indicating that both starbursts and AGN are physical drivers of galactic outflows. In this study, we do not find a connection between the current SFR (or SFR normalised by the main sequence, following Avery et al 2021) and Δ𝜎 (see Varidel et al 2020), so there is no direct evidence linking the physical drivers of gas outflows and the impact of outflows on gas kinematics.…”
Section: Discussionmentioning
confidence: 99%
“…Avery et al (2021), however, reported that the mass outflow rates depend on the luminosity of AGN and SFR, indicating that both starbursts and AGN are physical drivers of galactic outflows. In this study, we do not find a connection between the current SFR (or SFR normalised by the main sequence, following Avery et al 2021) and Δ𝜎 (see Varidel et al 2020), so there is no direct evidence linking the physical drivers of gas outflows and the impact of outflows on gas kinematics. Another possible explanation for enhanced Δ𝜎, especially valid for LINER, is dynamically-warm diffuse ionised gas powered by evolved stars (Belfiore et al 2016;Law et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation